2019
DOI: 10.1002/ecs2.2796
|View full text |Cite
|
Sign up to set email alerts
|

Extent and drivers of vegetation type conversion in Southern California chaparral

Abstract: The native chaparral shrublands of Southern California support exceptional biodiversity and provide critical ecological services, but increased fire frequency threatens to extirpate much of the chaparral due to long regeneration times needed between fires for many species. When short fire intervals inhibit shrub recovery, this favors invasion of exotic herbaceous species, and vegetation type conversion from woody shrubs to grassland is therefore a serious ecological concern in this biodiversity hotspot. Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 49 publications
(119 reference statements)
5
52
0
Order By: Relevance
“…This could be due to vegetation trends being more strongly correlated with moisture gradients driven by elevation than by distance from the coast. Indeed, Meng et al (2014) and Syphard et al (2019b) found elevation to be a strong driver of vegetation change with more chaparral conversion occurring at lower elevations. Analysis by Storey et al (2019) included a more extensive range of chaparral stands in southern California and found vegetation change was greatest in the eastern portion of their study region and at higher elevations and was a result of drought and fire interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be due to vegetation trends being more strongly correlated with moisture gradients driven by elevation than by distance from the coast. Indeed, Meng et al (2014) and Syphard et al (2019b) found elevation to be a strong driver of vegetation change with more chaparral conversion occurring at lower elevations. Analysis by Storey et al (2019) included a more extensive range of chaparral stands in southern California and found vegetation change was greatest in the eastern portion of their study region and at higher elevations and was a result of drought and fire interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A single short-interval fire, however, does not always lead to chaparral conversion. Previous work with remotely sensed data suggest that water availability (Park et al, 2018, Syphard et al, 2019a), elevation (Meng et al, 2014), and mean annual temperature (Storey et al, 2021) explain more variation among chaparral stand recovery (although also see Syphard et al (2019b)). These studies utilized imagery with 30-m spatial resolution and/or datasets with a 30-m scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where the fire return interval of shrublands approximates the historic fire return interval (average 55 years for low-elevation shrubland) [8,14,15], shrub cover recovers after 10-14 years, while biomass keeps accumulating [16,17]. However, in many areas, the fire return interval has decreased, often in conjunction with an increase in non-native plant species, drought, and nitrogen deposition [18][19][20]. Under these conditions, post-fire biomass recovery can be impeded and, in some cases, may result in type conversion from native shrubland to non-native grassland [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, in many areas, the fire return interval has decreased, often in conjunction with an increase in non-native plant species, drought, and nitrogen deposition [18][19][20]. Under these conditions, post-fire biomass recovery can be impeded and, in some cases, may result in type conversion from native shrubland to non-native grassland [20].…”
Section: Introductionmentioning
confidence: 99%